Volatility Exchange Rate and Economic Growth: Insight from ASEAN Member Countries - Gatot Nazir Ahmad; Haryo Kuncoro; Harmuzan Tazril; Dicky Iranto (Scientific Annals of Economics and Business)
This study aims to determine the effect of exchange rate volatility on economic growth in the ASEAN member countries (Indonesia, Thailand, Vietnam, and Cambodia) through investment. Based on the previous studies, the researcher focuses on developing the initial research analysis because it can control different company levels' characteristics and then determine the impact of exchange rate changes on economic growth mediated by investment. There is a limited analysis of whether exchange rate movements encourage overall investment in this study's particular direction. The author's primary focus is whether the export or import channels or both play an essential role in determining a company's investment. This study's population is in ASEAN member countries that have been published by the World Bank (https://www.worldbank.org/) and continue to exist during the period 1998-2019. The sample selection in this study used a purposive sampling method. Some of the ratio data were available in the financial report summary. The analysis method used in the study is the path analysis.